THE GOVERNMENT CONTROL SYSTEM OF INNOVATIVE DEVELOPMENT OF UKRAINE’S HELTHCARE - Yurynets, Z. V.; Yurynets, R V.; Petrukh, O. A. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
The article deals with the theoretical bases of forming of the government control system of innovative development of Ukraine’s healthcare. It has been found that innovative healthcare processes are slowly developing and need to be resolved. Among the regulatory influences, state regulation is most effective in the field of market transformations. The main purpose of the article is to identify the levels of governance and healthcare providers, to group and to characterize the state regulation system of healthcare innovative development. The article deals with the levels of hierarchical control (macro level, meso level, micro level, nano level) and the corresponding subjects involved in the process of innovative development of healthcare The government control system of innovative development of healthcare can be described as a continuum of functional components, properties of objects, and relations between them in order to achieve primary objectives of innovative development in the sphere. Application of clear and effective tool of government control of innovative development in healthcare is needed for realization of the government control system of innovative development of the aforementioned field and public policy. We state, that the signs of the government control system of innovative development of health protection sphere has been distinguished as follows: aims, main reference-point, directions and tasks of government control, general criteria of the government control system of innovative development of healthcare, methods of state stimulation of innovative activity, instruments of government control of innovative development of healthcare, evaluation criteria of instruments of government control. We established that the achievement of strategic aims of innovative development of healthcare is impossible without effective government control of innovative processes. Innovative processes are the specific, scale, difficult and many-sided object of adjusting. It requires the use of non-spread functions, methods of influence for effective development of healthcare.